Importancia de las actividades de aprestamiento para la lectoescritura en los estudiantes de primer grado de educación general básica de la Academia Naval Amazonas del cantón Durán período lectivo 2018-2019 - Jiménez Pazmiño, Wendy María (2019)
The study that is presented, allows to know the importance of readiness activities for reading and writing in the first grade students of general basic education. Literacy is a natural and gradual process that must be well oriented in the first years of schooling so that its subsequent learning is successful and develops normally. In the development of the research project, a descriptive methodology based on a field investigation was used to obtain the data through the application of a survey. It was concluded that, the development of the importance of readiness of writing and carry many motor, cognitive and socialization consequences, the same ones that will determine the future academic learning of the scholar…………..